Expression of mouse MGAT in Arabidopsis results in increased lipid accumulation in seeds - Anna eEl Tahchy; Anna eEl Tahchy; James Robertson Petrie; James Robertson Petrie; Pushkar eShrestha; Pushkar eShrestha; Thomas eVanhercke; Thomas eVanhercke; Surinder eSingh; Surinder eSingh (Frontiers in Plant Science, 2015)
Worldwide demand for vegetable oil is projected to double within the next thirty years due to increasing food, fuel and industrial requirements. There is therefore great interest in metabolic engineering strategies that boost oil accumulation in plant tissues, however, efforts to date have only achieved levels of storage lipid accumulation in plant tissues far below the benchmark to meet demand. Monoacylglycerol acyltransferase (MGAT) is predominantly associated with lipid absorption and resynthesis in the animal intestine where it catalyses monoacylglycerol (MAG) to form diacylglycerol (DAG), and then triacylglycerol (TAG). In contrast plant lipid biosynthesis routes do not include MGAT. Rather, DAG and TAG are either synthesized from glycerol-3-phosphate (G-3-P) by a series of three subsequent acylation reactions, or originate from phospholipids via an acyl editing pathway. Mouse MGATs 1 and 2 have been shown to increase oil content transiently in Nicotiana benthamiana leaf tissue by 2.6 fold. Here we explore the feasibility of this approach to increase TAG in Arabidopsis thaliana seed. The stable MGAT2 expression resulted in a significant increase in seed oil content by 1.32 fold. We also report evidence of the MGAT2 activity based on in vitro assays. Up to 3.9 fold increase of radiolabelled DAG were produced in seed lysate which suggest that the transgenic MGAT activity can result in DAG re-synthesis by salvaging the MAG product of lipid breakdown. The expression of MGAT2 therefore creates an independent and complementary TAG biosynthesis route to the endogenous Kennedy pathway and other glycerolipid synthesis routes.